Neuroanatomical and behavioral deficits in mice haploinsufficient for Pericentriolar material 1 (Pcm1). (September 2015) - Zoubovsky, Sandra; Oh, Edwin C.; Cash-Padgett, Tyler; Johnson, Alexander W.; Hou, Zhipeng; Mori, Susumu; Gallagher, Michela; Katsanis, Nicholas; Sawa, Akira; Jaaro-Peled, Hanna
Highlights: First study of the effects of Pcm1 haploinsufficiency on brain structure and behavior. Pcm1 +/− mice had a slightly smaller brain compared to wild-type mice. Pcm1 +/− mice were impaired in the social novelty test, but not in novel object recognition. Abstract: The pericentriolar material (PCM) is composed of proteins responsible for microtubule nucleation/anchoring at the centrosome, some of which have been associated with genetic susceptibility to schizophrenia. Here, we show that mice haploinsufficient for Pericentriolar material 1 ( Pcm1 +/− ), which encodes a component of the PCM found to bear rare loss of function mutations in patients with psychiatric illness, manifest neuroanatomical phenotypes and behavioral abnormalities. Using ex vivo magnetic resonance imaging of the Pcm1 +/− brain, we detect reduced whole brain volume. Pcm1 mutant mice show impairment in social interaction, specifically in the social novelty phase, but not in the sociability phase of the three-chamber social interaction test. In contrast, Pcm1 +/− mice show normal preference for a novel object, suggesting specific impairment in response to novel social stimulus. In addition, Pcm1 +/− mice display significantly reduced rearing activity in the open field. Pcm1 +/− mice behave normally in the elevated plus maze, rotarod, prepulse inhibition, and progressive ratio tests. Together, our results suggest that haploinsufficiency at the Pcm1 locus can induce a range of neuroanatomical and behavioral phenotypes that support the candidacy of this locus in neuropsychiatric disorders.